Inductive loops for sensing position as signature signals - Larbani, Sofiane; Abdul Malik, Noreha; Nordin, Anis Nurashikin; Khan, Sheroz; Shobaki, Mohammed M. (IOP Publishing, 2013)
In this paper, an inductive sensing technique made of a special shaped inductive loop is proposed. The inductive loop has an inner turn fitted within an outer turn, making a total inductance value 100μH. This loop is made to be shown with balanced response using three capacitance values of 0.068μF each when a sinusoidal voltage source of 5V peak-to-peak is applied. The variation of the relative permeability of the inductance of the inductive loop (AL) results in a variation of the overall inductance value (L+AL), that causes the output signal to change in term of shape and amplitude for variation of total inductance sweep over a given period of time. As a result of change in inductance value (lμH) there is a correspondence increase of 300mV. Theoretical derivations have showed in close agreement with the simulation plots obtained using Multisim software.